Design and Implementation of Web Service for Laundry Service Payment at RAZ-Q Laundry Samarinda - Mallala, Syamsudin; Pukeng, Ahmad Fahrijal; Nursobah, Nursobah (PT Mattawang Mediatama Solution, 2024)
The advancement of technology has facilitated access to information and various applications spanning desktop, web, and mobile platforms, becoming an integral part of everyday life. Among these platforms, websites are the most widely used. The web is widely used for business purposes. One of the common businesses is laundry services, which has become essential for individuals with busy schedules, such as workers and students. Busy daily activities make the need for clean clothes a top priority. However, the existence of many laundry service providers creates intense competition and difficulties for new consumers in finding the right service. This research examines a web services-based laundry service designed to help consumers find and book quality laundry services in their vicinity. It also provides process monitoring features and estimated time for clothes pickup. For laundry service owners, these web services offer opportunities to improve their business. This research uses the Waterfall method of software development, including the stages of analysis, design, coding, and testing. Use case diagrams were used to model the interaction between actors in the application. The web interface is designed according to user needs. The result of this research is web services that can help consumers find and order laundry services easily and efficiently. Blackbox testing is conducted to ensure that all designed functions run properly. This application has the potential to help laundry service owners increase their income. Application development is done using Visual Studi Code with PHP Native programming language and MySQL as database management.